Analysis of shared underlying mechanism in neurodegenerative disease - Butler, Rickeem; Bradford, David; Rodgers, Kathleen E. (Frontiers in Aging Neuroscience, 2022)
In this review, the relationship between bioenergetics, mitochondrial dysfunction and inflammation will be and how they contribute to neurodegeneration, specifically in Alzheimer’s Disease (AD), Amyotrophic Lateral Sclerosis (ALS), and Multiple Sclerosis (MS) will be reviewed. Long term changes in mitochondrial function, autophagy dysfunction, and immune activation are commonalities shared across these age-related disorders. Genetic risk factors for these diseases support an autophagy-immune connection in the underlying pathophysiology. Critical areas of deeper evaluation in these bioenergetic processes may lead to potential therapeutics with efficacy across multiple neurodegenerative diseases.